The Effect Of Prone Position On Oxygen Saturation In Premature Infants - Mahmud Gunggung Saputro; Akhmad Rifai; Sumardino Sumardino; Sugiyarto Sugiyarto (Universitas Islam Jember, 2023)
Preterm labor is labor that occurs when the gestational age is less than 37 weeks so that it can result in respiratory distress syndrome. One of the signs and symptoms is a decrease in oxygen saturation. If the oxygen saturation is low, it can cause reduced tissue oxygen. One way to increase oxygen saturation in premature babies is the prone position. This Literature Review discusses the increase in oxygen saturation in premature infants who are given the prone position. This research uses a literature review study with a search strategy using the PICOS framework in the pubMed, researchgate, garuda, and google scholar databases in the 2018-2023 timeframe. The results of the ten articles analyzed were the duration of the pronation position between 1-3 hours with monitoring of oxygen saturation in the first and second 10 to 60 minutes. There is an effect of the prone position on increasing oxygen saturation in premature infants with a significance value of p<0.05. The average oxygen saturation of premature babies after being given a prone position has increased by 94% -99%. There is an increase in oxygen saturation in premature infants after the prone position is performed.